Autoscopic phenomena as an atypical psychiatric presentation of Huntington's disease: A case report including longitudinal clinical and neuroimaging data. (April 2020) - Martínez-Horta, Saul; Perez-Perez, Jesús; Pagonabarraga, Javier; Sampedro, Frederic; Horta-Barba, Andrea; Blanke, Olaf; Kulisevsky, Jaime
Abstract: Huntington's disease (HD) is a monogenetic neurodegenerative disease prototypically characterized by the progressive presentation of motor abnormalities, cognitive deterioration and neuropsychiatric symptoms. Even when the disorder is diagnosed based on the presence of unequivocal motor symptoms, subtle cognitive and behavioral changes emerge decades before the first motor manifestations. Here we present the atypical case of a young premanifest gene-mutation carrier who developed progressive complex autoscopic phenomena (feelings of presence, out of body experience, and heautoscopic hallucinations). To our knowledge, this is the first report of these symptoms in the context of HD. Considering the availability of serial neurologic, neuropsychological and neuroimaging data collected before and after the presentation of these symptoms, this case provides new insights into the brain mechanisms leading to autoscopic phenomena and atypical phenotypes that may occur in HD.